Motivasi Partisipasi Politik Perempuan Pada Pemilu Legislatif 2019 di Kabupaten Ogan Komering Ulu - Bela, Herwin Sagita; Utama, Alip Susilowati (Jurnal Pemerintahan dan Politik)
AbstractPolitical participation is a measure of the success of the democratization process because in political participation there is citizen control of government. At present political participation which is still an interesting theme to be investigated is women's political participation. This is inseparable from the existence of the affirmative action movement which wants equal opportunities for women to participate in the political constellation. At present, the influence of political participation in the regions is an important note for central government policy. Therefore, it is important to know the prospects for women's political participation in the region. The results showed that the affirmative action policy actually has a side that can be beneficial but also detrimental to women and political parties. Many of the opportunities with this policy are not exploited because in fact many women do not have the desire to participate in political contestation. This is inseparable from the social support from women in the form of social, economic and cultural support. Most women will think long when it comes to family permits and the economic conditions of the family and culture that surrounds it so far. Therefore, the party also experienced difficulties in recruiting and cadre of party members because most were constrained by these factors although in terms of women's political orientation, they understood and had knowledge of the political system although they were not able to influence gender responsive policies at the district level.Keywords : Prospects, Motivation, Women's Political ParticipationAbstrakÂ Partisipasi politik merupakan tolak ukur keberhasilan proses demokratisasi karena dalam partisipasi politik terdapat kontrol warga negara terhadap pemerintahan. Saat ini partisipasi politik yang masih menjadi tema yang menarik untuk diteliti adalah partisipasi politik perempuan. Hal ini tidak terlepas dari adanya gerakan affirmative action yang menginginkan adanya peluang yang sama bagi perempuan untuk ikut serta dalam konstelasi politik. Saat ini juga, pengaruh dari partisipasi politik di daerah menjadi catatan penting bagi kebijakan pemerintah pusat. Oleh sebab itu, penting untuk mengetahui bagaimana prospek partisipasi politik perempuan di daerah. Hasil penelitian menunjukkan bahwa kebijakan affirmative action sebenarnya memiliki sisi yang dapat menguntungkan namun juga merugikan bagi perempuan dan partai politik. Peluang dengan adanya kebijakan ini banyak tidak termanfaatkan karena pada faktanya banyak perempuan tidak memiliki keinginan untuk berpartai dan ikut dalam kontentasi politik. Hal ini tidak terlepas dari dukungan sosial dari perempuan berupa dukungan sosial, ekonomi dan budaya. Kebanyakan perempuan akan berpikir panjang jika menyangkut izin keluarga dan kondisi perekonomian keluarga dan budaya yang melingkupinya selama ini. Oleh sebab itu, partai juga mengalami kesulitan dalam perekrutan dan pengkaderan anggota partai karena sebagian besar terkendala dengan faktor tersebut meskipun dari sisi orientasi politik perempuan, mereka memahami dan memiliki pengetahuan tentang sistem politik meskipun belum mampu mempengaruhi kebijakan yang bersifat responsif gender di tingkat Kabupaten.Kata kunci : Prospek, Motivasi, Partisipasi Politik Perempuan